Severe COVID-19 and Sepsis: Immune Pathogenesis and Laboratory Markers - Mai M. Zafer; Hadir A. El-Mahallawy; Hossam M. Ashour (Microorganisms, 2021)
The ongoing outbreak of the novel coronavirus disease 2019 (COVID-19), induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has taken a significant toll on people and countries all over the world. The pathogenesis of COVID-19 has not been completely elucidated yet. This includes the interplay between inflammation and coagulation which needs further investigation. The massive production of proinflammatory cytokines and chemokines results in the so-called cytokine storm, leading to plasma leakage, vascular hyperpermeability, and disseminated vascular coagulation. This is usually accompanied by multiorgan failure. The extensive changes in the serum levels of cytokines are thought to play a crucial role in the COVID-19 pathogenesis. Additionally, the viral load and host inflammation factors are believed to have a significant role in host damage, particularly lung damage, from SARS-CoV-2. Interestingly, patients exhibit quantitative and qualitative differences in their immune responses to the virus, which can impact the clinical manifestation and outcomes of COVID-19. There needs to be a better understanding of the dynamic events that involve immune responses, inflammatory reactions, and viral replication in the context of the COVID-19 infection. Here, we discuss the main aspects of COVID-19 pathogenesis while supporting the hypothesis that inflammatory immune responses are involved in the progression of the disease to a more critical and fatal phase. We also explore the similarities and differences between severe COVID-19 and sepsis. A deeper understanding of the COVID-19 clinical picture as it relates to better-known conditions such as sepsis can provide useful clues for the management, prevention, and therapy of the disease.